A 15-year retrospective review of urodynamic studies in Children at Red Cross War Memorial Childrens Hospital (RCWMCH), Cape Town, South Africa - Mosalakatane, Thembisile Dintle (Department of Paediatrics and Child Health, 2023)
Background: Despite the undeniable diagnostic benefits of urodynamic studies (UDS), their adoption into clinical practice in Africa has been slow. This study aimed to review the use of invasive UDS in children at a tertiary paediatric hospital in South Africa. Methods: A retrospective analysis of 1108 UDS was conducted. Patient demographic characteristics, primary diagnosis, indication and urodynamic outcomes were reviewed. Presence of urodynamic high-risk features were documented, and a comparison was made between the first study and follow-up study. Results: This study revealed increasing trends in the use of UDS from 2015. Referrals were from Urology (37.7%), Spinal defects clinic (34.4%), Nephrology (20.8%) and other departments (7.0%). The most common reason for referral was review of medical treatment (36.5%). Spinal dysraphism (58.3%) accounted for the majority of conditions seen. Majority (59.1%) of the patients were receiving more than one type of bladder treatment at the time of their first study, with clean intermittent catheterisation (46.5%) being the most common form of bladder management. 97.5% of studies were performed using transurethral bladder catheterization. Urodynamic diagnosis was neurogenic in 74.0%, anatomical (12.2%), functional (8.8%) and normal (5.0%). There was statistically significant improvement in bladder compliance, detrusor leak point pressure and detrusor sphincter dyssynergia between the first study and a subsequent study following therapeutic intervention. Conclusion: The unique ability of UDS to demonstrate changes in detrusor pressures, which is a common reason for therapy failure, makes UDS an invaluable tool in the diagnosis and management of children with lower urinary tract dysfunction.